2013
DOI: 10.1002/gbc.20049
|View full text |Cite
|
Sign up to set email alerts
|

History of nutrient inputs to the northeastern United States, 1930–2000

Abstract: [1] Humans have dramatically altered nutrient cycles at local to global scales. We examined changes in anthropogenic nutrient inputs to the northeastern United States (NE) from 1930 to 2000. We created a comprehensive time series of anthropogenic N and P inputs to 437 counties in the NE at 5 year intervals. Inputs included atmospheric N deposition, biological N 2 fixation, fertilizer, detergent P, livestock feed, and human food. Exports included exports of feed and food and volatilization of ammonia. N inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…We used data from Hale et al . [] for inputs of N and P. They estimated inputs to NE counties ( N = 437) at 5 year time steps from 1930 to 2002 following the mass balance approach of Green et al . [].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from Hale et al . [] for inputs of N and P. They estimated inputs to NE counties ( N = 437) at 5 year time steps from 1930 to 2002 following the mass balance approach of Green et al . [].…”
Section: Methodsmentioning
confidence: 99%
“…Inputs included fertilizer, livestock manure, human waste, atmospheric deposition (N only), biological N 2 fixation (N only), and detergent P. See Hale et al . [] for details on data sources, calculations, and assumptions. Nutrient inputs were categorized as point sources, organic nonpoint sources, and inorganic nonpoint sources following Green et al .…”
Section: Methodsmentioning
confidence: 99%
“…Portions of LIS have been observed to exhibit sea sonally high pCO 2 conditions in excess of 2,500 µatm (Wallace et al, 2014), well above conditions in typical oceanic waters, which are commonly near that of the atmosphere (400 µatm). Within the Northeast, the import of nitrogen has gradually increased since the early 1900s (Hale et al, 2013), presumably increasing the export to coastal waters. Roman et al (2000) found that nitro gen at eight estuaries in the Northeast increased by a factor of over three since 1900, with northern estuaries, such as those in Maine, showing lower average annual concentrations than more south ern systems, but continuing to increase due to population growth (Wilson and Fischetti, 2010).…”
Section: Urbanized Estuaries Of the New England/nova Scotia Regionmentioning
confidence: 99%
“…Nitrogen loading for Narragansett Bay may have increased by 250% over the past 150 years due to the increase in the "sewered" human popula tion and the use of agricultural fertilizer (Vadeboncoeur et al, 2010). There may be cause for optimism in the Northeast, however, given declines in nitrogen loadings due to reduc tions in imports of livestock feed, and of significant recent decreases in atmo spheric deposition (Hale et al, 2013 (Latimer et al, 2014).…”
Section: Urbanized Estuaries Of the New England/nova Scotia Regionmentioning
confidence: 99%
“…Although fertilizer use dropped notably in many areas of North America in the 1980s and 1990s (eg eastern Canada, northeastern US; MacDonald and Bennett ; Hale et al . ), at the global scale pesticide use has risen dramatically (Gilbert ). Glyphosate – a phosphonic acid with the formula C 3 H 8 NO 5 P, also known as N ‐(phosphonomethyl)glycine – is now the most widely used pesticide worldwide, ranking first in both sales and treated surface area (Nadin ; Environment Canada ).…”
mentioning
confidence: 99%